Retirement Preparation among Operational-Level Employees: A Case study of an Industrial Factory - พิมพาภรณ์, ณัฐชฎา; ถาพินนา, ชัยยะเนตร; เสมศรี, ศุภโชค; อื้อฉาว, ภานุวัฒน์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This qualitative study aimed to explore retirement preparation among operational-level employees in an industrial organization. The study population and sample comprised employees from a selected case-study company aged 45 years and above. Fifteen participants were recruited through purposive sampling, supplemented by the snowball sampling technique. Data were collected using in-depth interviews. A semi-structured interview guide was employed as the research instrument and was examined for content validity using the Index of Item-Objective Congruence (IOC) by three experts.  Findings indicated that participants primarily understood retirement as the termination of employment or the cessation of work, in accordance with company regulations and/or labor-related provisions. Retirement age was perceived to be determined by employers or relevant authorities, commonly at 55 or 60 years in both public and private sectors. The most frequently cited source of retirement-related information was the company’s internal communication and announcements. With regard to retirement preparation, most participants reported that financial readiness was their main priority. Common practices included saving, setting aside emergency funds for post-retirement living, and planning and controlling non-essential expenditures. Participants also described preparation related to health maintenance and planning for post-retirement work. In terms of perceived consequences, positive outcomes included having time to rest after many years of work, spending more time with family, living closer to nature, and achieving a lifestyle aligned with personal plans. Negative outcomes included reduced income, financial insufficiency to repay outstanding debts, inadequate monthly income, limited social interaction, and physical decline associated with prolonged work exposure. Most participants expressed an intention to engage in self-employment after retirement, such as farming consistent with the sufficiency economy philosophy, operating small-scale businesses, or continuing family enterprises. Only a small proportion indicated no intention to pursue any occupation after retirement.